Pre-emptive 8 mg dexamethasone and 120 mg etoricoxib for pain prevention after periodontal surgery: A randomised controlled clinical trial - Kranti Konuganti; Mani Rangaraj; Anjana Elizabeth (Wolters Kluwer Medknow Publications, 2015)
Several anti-inflammatory drugs have been used to reduce pain and discomfort after periodontal surgeries. This study evaluates the efficacy of using etoricoxib and dexamethasone for pain prevention after open-flap debridement surgery. In this study, 60 patients who were undergoing open flap debridment surgery were randomly assigned to receive a single dose preoperative medication 1 hour prior to surgery. The patients were divided into three groups. In Group 1, 20 patients were given placebo drug orally. In Group 2, 20 patients were given 8 mg Dexamethasone orally and in Group 3, 20 patients were given 120 mg Etoricoxib orally. Patients were instructed to complete a pain diary hourly for the first 8 hours after each surgery and three times a day on the following 3 days. The four point verbal rating scale (VRS 4) and Numerical rate scale were used to assess discomfort. Post-operative Assessment of Pain and Discomfort showed that persistent discomfort and pain were found to be more in the placebo group compared to dexamethasone and etoricoxib group. The adoption of a preemptive medication protocol using either etoricoxib or dexamethasone may be considered effective for pain and discomfort prevention after open-flap debridement surgeries.